Method development plan works in the project harvest grain - Тимочко, Василь Олегович (Technology audit and production reserves, 2012)
The procedure of plan forming are worked out as to harvesting of grain crops in agricultural enterprise. The procedure on the base of imitation simulation foresees possibility to use of additional combines of another owners